About related medicines with the 2019 pandemic - Musina A. S.; Mukhamet A. E.; Gorbulicheva E. P. (World Scientific Reports, 2023)
This paper examines the medicines proposed for the treatment коронaвируса of the COVID-2019 coronavirus, which was the main crisis of 2019 that shook the whole world. It was revealed that thecausative agent of COVID-2019 is a certain class вирусов, относящихof viruses classified as infectious agentsthat enter the body’s cells and cause the disease. Depending on the structure, different types of viruses are distinguished: RNA and DNA-containingviruses